(untitled) (Tempo e Argumento, 2022)
In the refuge of foundlings and orphans of Montevideo there was a circular lopende band from 1818 until 1934 (a year in which it was forbidden). In this torno or rotary device, people used to leave babies with signs such as letters, medals, pictures, among other things. This article analyzes such objects through the perspective of the history of emotions as an example of values and social practices of morality in a determined period of time. It visibilizes and analyses these signals and the symbolic language used in such practices, approaching them as cipher messages of an intimate conversation between families and progeny. 90% of the babies brought such signs, and the legal period for recovering them was two years. During that period only 30% of the childs were recovered by their family.